Surfactant-assisted aqueous extraction of residual oil from palm-pressed mesocarp fibre - Ramly, Nor Hakimah (2017)
Surfactant-assisted aqueous extraction process (SAAEP) has been proposed as a green alternative for the extraction of oil from various plant materials. While most oil is extracted through hexane-based technique, concern about environmental and health effects from hexane extraction has led to an increased interest in the development of green SAAEP for edible oil application. Therefore, the aim of this study is to explore the potential of SAAEP using Tween 80, a food-grade surfactant, for the recovery of residual oil from palm-pressed mesocarp fibre (PPMF). First, the phase behaviour of Tween 80 solution and crude palm oil (CPO) were studied by analysing the interfacial tension (IFT), droplet size, viscosity and phase inversion temperature (PIT). The IFT value was evaluated by varying Tween 80 concentration (0.001-30w/v %), NaCl concentration (0.5-6w/v%), temperature (50-70C), and fructose concentration (1-10w/v%). The lowest IFT of 0.253 mN/m was obtained using at least 0.5w/v% Tween 80, 6w/v% NaCl, and temperature of 60C while the addition of fructose does not affect the IFT. The emulsion obtained has a droplet size of 4183.8 nm and viscosity of 7.38 cp. At high concentration of Tween 80 (30w/v%), the emulsion size was determined in nano-size-range but the viscosity of emulsion is very high (232.15 cp). Furthermore, emulsion of CPO and Tween 80 did not show the presence of phase inversion temperature (PIT) indicating that ultra-low level IFT (10-3 mN/m) was not achieved with increase in temperature. Microscopic study by TEM and light microscopy reveals that the oil in PPMF resides inside the broken cells of fibrils with a small amount of oil attached on the surface of the fibres. Application of the Tween 80 solution in the extraction of oil from PPMF shows that the highest oil extraction (47.4 %) was obtained at 1 % w/v of Tween 80, 6w/v% of NaCl, solid to liquid ratio of 8g of PPMF: 200 mL of Tween 80 solution, 30 min of extraction time at 60C of extraction temperature. To improve the extraction yield further, attempt was made to mix Tween 80 with other green surfactants and interfacial properties was studied. Tween 80 was mixed with Emereen 1018 and Pluronic F108 in a binary surfactant system that theoretically can enhance the interaction with CPO. However, Tween 80/Emereen 1018 mix and Tween 80/Pluronic F108 mix can only produce the lowest IFT value of 0.64 mN/m and 0.69 mN/m respectively. As the binary system did not enhance the IFT reduction, Span 20 and Span 80 were added into the binary mixtures as lipophilic linkers. However, these lipophilic linkers also cannot experimentally enhance the IFT reduction further. Therefore, it can be concluded that single surfactant system using Tween 80 can be proposed as the potential extraction system for residual oil from PPMF. However, the studied mixed surfactant system did not assist in further reduction of IFT and thus is not expected to contribute into further increase of oil extraction efficiency.